TICK-BORNE VIRUSES OF WEST PAKISTAN: I. ISOLATION AND GENERAL CHARACTERISTICS - BEGUM, FATIMA; WISSEMAN, C. L.; TRAUB, R. (Oxford University Press, 1970)
Begum, F., C. L. Wisseman, Jr. (Dept. Microbiology, School of Medicine, Univ. of Maryland, Baltimore, Md. 21201) and R. Traub. Tick-borne viruses of West Pakistan. I. Isolation and general characteristics. Amer. J. Epid., 1970, 92: 180–191.—Between 1964 and 1966, hard ticks collected from a great variety of wild and domestic mammals in widely separated regions of West Pakistan, representing an extreme range of habitats, were examined for the presence of viral agents by the inoculation of tick suspensions intracerebrally into suckling mice. From 208 pools inoculated, 8 viral agents with the general characteristics of arboviruses and representing at least 4 distinct serologically unrelated groups, where isolated. One group appeared to be represented by 2 related but separable serotypes. Habitats from which the viruses were isolated included semi-desert and artificial forest on the plains, and coniferous forest, subarctic terrain and mountain desert in the Himalaya Mountains. Mammalian hosts of the ticks consisted of domestic cows, goats and camels as well as the rodents, Alficola roylesi, Tafera indica and the pika, Ochotona roylei. Ticks in the positive pools consisted of the genera, Ixodes, Hyalomma, Rhipicephalus and Boophilus .